THE STUDENTS’ PERCEPTION TOWARDS THE USE OF GOOGLE MEET IN MICRO TEACHING - Pitrah Ulwiah; Haryanto Atmowardoyo; M. Tahir (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aims to determine students' perceptions of the use of google meet in micro-teaching. The researcher applied mixed quantitative and qualitative methods. to achieve the purpose of the study, the data was collected in the form of a Likert questionnaire, and interview. The subjects of this study were students of the Makassar State University, particularly in the English Education Department academic 2022/2023. The sample of the questionnaire is 30 students and Interviews of 10 students were taken using the voluntary sampling technique/non-probability sampling technique. The results of data analysis show that (1) positive student perceptions of the use of Google meet application in micro-teaching with the classification, 7(23%) students classified Strongly positive, 12 (40%) students classified Positive, 9 (9%) students are classified as Medium, 2 (2%) students are classified as Negative and not there are students who are classified as strongly negative. (2) Student explanations in interviews regarding the perception of using google meet explained that google meet is a good and interesting online learning tool, and has good features that really support micro teaching-learning in this pandemic era. Even though there is a pandemic, students can still learn micro-teaching through google meet because in google meet learning students and lecturers can still interact and discuss well like in an offline class.